2011
DOI: 10.5007/2175-7925.2011v24n4p1
|View full text |Cite
|
Sign up to set email alerts
|

<b>Atividade antimicrobiana do óleo essencial de alecrim-pimenta e do extrato bruto seco do barbatimão diante de bactérias isoladas do leite</b><br>DOI:10.5007/2175-7925.2011v24n4p1

Abstract: ResumoO objetivo deste trabalho foi avaliar a atividade antimicrobiana in vitro do óleo essencial do Lippia sidoides (OELs), conhecido popularmente como "alecrim-pimenta", e do extrato bruto seco do Stryphnodendron adstringens (EBSSa), ou "barbatimão", contra bactérias isoladas do leite total de rebanho, provenientes de unidades agrícolas familiares do norte de Minas Gerais. O EBSSa foi obtido a partir da casca do vegetal por extração estática em etanol 99,9% por oito dias. O OELs foi obtido por meio da hidrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Our results are in agreement with data in the literature, which show the bactericidal activity of the L. origanoides essential oil against various microorganisms (Veras et al 2014) and suggests that this concentration is most efficient in oils obtained from plants collected between the months of December and May. The results obtained in other studies using the essential oil of L. origanoides extracted from plants from the North of Minas Gerais also concur with the optimal concentration found in this study (Castro et al 2011, Costa et al 2011, Pinho et al 2012.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in agreement with data in the literature, which show the bactericidal activity of the L. origanoides essential oil against various microorganisms (Veras et al 2014) and suggests that this concentration is most efficient in oils obtained from plants collected between the months of December and May. The results obtained in other studies using the essential oil of L. origanoides extracted from plants from the North of Minas Gerais also concur with the optimal concentration found in this study (Castro et al 2011, Costa et al 2011, Pinho et al 2012.…”
Section: Discussionsupporting
confidence: 83%
“…Morais (2009) suggested that genetic factors, age of the plant and climatic and environmental factors, as well as the period of the year the plants were collected, may cause significant alterations in the production of secondary metabolites influencing the composition of essential oils and thereby the oil's antimicrobial effect. According to Costa et al (2011), the essential oil of L. origanoides inhibited the growth of S. aureus and E. coli with inhibition halos of 8.2 and 23.2 mm respectively at a concentration of 160µL/mL. Klancnik et al (2010) tested different essential oils against different bacteria and concluded that despite diffe- Hematological and biochemical parameters measured in the serum of Wistar rats treated chronically using oral vehicle (Control, n=5) or with daily doses of 120mg/kg of Lippia origanoides essential oil (n=5) for 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al (2011) used extract obtained by methodology different from the one adopted in this study to evaluate growth of E. coli and S. aureus isolated from bovine milk, and Pinho et al (2012) evaluated the activity of S. adstringens extract obtained from leaves in these same microorganisms. These studies showed that concentrations ranging from 25 to 500mg/mL of dried crude S. adstringens extract did not inhibit E. coli growth (Costa et al 2011, Pinho et al 2012). Concentrations higher than or equal to 300mg/mL can inhibit S. aureus growth (Pinho et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Estudos realizados com óleo essencial de alecrim-pimenta provenientes da mesma área de reserva nativa do ICA-UFMG na região Norte de Minas Gerais apresentaram resultados semelhantes quanto aos compostos majoritários, (10) carvacrol, seguido de (03) p-cimeno, (7) timilmetil éter, (11) cariofileno e o γ-terpineno (05) (Costa et al 2011, Castro et al 2011, Queiroz et al 2014. Resultados relatados por autores em outras regiões do estado de Minas Gerais também são condizentes com os aqui descritos, ainda que os compostos tenham sido encontrados em percentual variável.…”
Section: Discussionunclassified
“…O potencial uso deste óleo essencial como antimicrobiano e antisséptico em saúde e produção animal, já foi confirmado in vitro em bactérias isoladas de leite e outros alimentos de origem animal (Costa et al 2011, Castro et al 2011, Queiroz et al 2014 , no entanto, pesquisas que avaliem a possível interferência de matéria orgânica na atividade ainda não foram publicadas.…”
Section: Introductionunclassified